Sintonia robusta do preditor Smith filtrado simplificado - Amaral, Daniel Lopes do (2025)
This document presents a robust synthesis methodology for the simplified filtered Smith predictor. The proposed unified tuning methodology for the simplified filtered Smith predictor is suitable for single-input single-output (SISO) processes with delay and multi-input multi-output (MIMO) processes with multiple delays. The proposed strategy preserves the filtered Smith predictor properties for stable, unstable, and integrative processes, simplifying the controller tuning by means of the state feedback decoupling for reference tracking and proposing an alternative method to the robustness filter parametrization. The procedure includes the disturbance model in the controller design to deal with the trade-off between the disturbance attenuation performance and the robust stability condition in the presence of the process model uncertainties. The simulation results illustrate the performance improvements when applying the proposed tuning compared to recently published cases. Furthermore, an experiment on a Neonatal Intensive Care Unity prototype effectively presents the potential of the unified tuning methodology when applied to an industrial process with practical features.